P472 Do chlamydia testing patterns in new zealand explain the high diagnosis rates?. (14th July 2019) - Righarts, Antoinette; Saxton, Peter; Gray, Andrew; Morgan, Jane; Green, J; Connor, Jennie; Dickson, Nigel
Abstract : Background: Diagnosis rates of Chlamydia trachomatis (CT) are high in New Zealand (NZ), affecting 4.1% of women and 1.5% of men aged 15–29 from national laboratory surveillance in 2014. National data also shows high rates of testing in women. We sought to understand CT testing by demographic and behavioural characteristics, information not available in routine surveillance. Methods: CT testing in the past year, sexual behaviour and demographic characteristics were self-reported by participants in the nationally representative 2014/15 NZ Health Survey (N= 10, 198 adults aged 16–74). Those aged 16–44 who had an opposite or same-sex sexual partner in the past year were included in this analysis. The prevalence of testing was calculated and Poisson regression used to investigate associations. Results: Of 3, 917 eligible participants, 5.5% (95% CI 4.2–7.2%) of men and 16.6% (14.7–18.8%) of women had tested in the past year, higher among 16–29 year-olds (11.2% [7.8–15.7%] of men and 29.5% [24.5–35.1%] of women). Having multiple partners (adjusted relative risk 3.79, 95% CI 1.50–9.54) and condomless sex (2.98, 1.49–5.96) were associated with more testing in men. For women, testing was positively associated with multiple partners (2.46, 1.71–3.53) and pregnancy (1.67, 1.22–2.27) and negatively associated with lower income and Asian ethnicity. Men and women reporting a same-sex partner had elevated, but not statistically significantly, testing rates. A general check-up was the most common reason for testing; however, 18.1% of men tested because their partner was diagnosed (versus 2.2% of women, p<0.001). Conclusion: The study confirms men are much less likely to be routinely tested than women in NZ, and more likely to test due to risk factors. A lack of routine CT testing among NZ men is one potential reason for ongoing high incidence and diagnosis rates among both sexes. Disclosure: No significant relationships.